Factors affecting parents' choices of functional foods targeted for children. (September 2016) - Annunziata, Azzurra; Vecchio, Riccardo; Kraus, Artur
Abstract: In recent years the link between diet and disease has become well established, with studies increasingly pointing to the role of diet in disease prevention, as well as its ability to prevent chronic diseases affecting children. As a consequence, there are ever more functional products specifically targeting children, marketed in terms of the benefits conferred on children's health as well as their potential in reducing the risk of disease. The current study aims to explore factors affecting parents' choices of suitable FFs for their children. The questions addressed in this paper concern how FFs for children are perceived by their parents and what driving factors affect their willingness to purchase FFs. The results from a web survey conducted in southern Italy on a sample of 365 parents of children aged from 1 to 10 years reveal that parents have a strong interest in functional nutrition for their children, even if their level of familiarity with these products is still low. Furthermore, multivariate analysis shows that the buying frequency of FFs targeting children is influenced by several variables, beyond socio‐demographics, generally related to parents' nutritional knowledge, and trust and familiarity with FFs. The paper provides some practical indications for both policy makers and marketers to build different strategies to improve communication on the nutritional and health benefits of FFs for children.